Lëttëra web platform: A game-based learning approach with the use of technology for reading competence - Leal Uhlig, Emilia Fernanda; Garza León, Carolina; Cruz Vargas, Xóchitl; Hernández Franco, Sheila; Portuguez-Castro, May (Frontiers in Education, 2023)
Today, reading literacy is crucial for young people in making decisions that have repercussions on their lives, especially after having experienced social isolation, such as that brought about by the Covid 19 pandemic. This study explores how technology, metacognition, and game-based learning can open spaces for the development of reading literacy in upper secondary school students, based on research conducted on the educational innovation Lëttëra, a web-based platform for the de-velopment of reading literacy. This platform is based on the reading processes of the PISA test using game-based learning using technology, which allows students to self-manage their strategy in an autonomous, flexible, and entertaining way, as it includes a highlighting system that guides critical reading to visualize the metacognitive processes that are carried out when reading. One hundred forty-nine responses from high school students in the standardized test Planea 2017 were reviewed to analyze whether there was a change in reading competence after using the Lëttëra platform. It was possible to identify significant differences and improvements after using the platform, especially in the literary text, information construction and argumentative text cate-gories. In addition, the authors analyzed students' motivation about technology, the interface, and the game system through a survey with descriptive statistics.